Mickey Mouse Clubhouse. Mickey's treat - Allwine, Wayne, 1947-2009; Anselmo, Tony.; Baker, Dee Bradley; Burton, Corey; Cummings, Jim, 1952-; Farmer, Bill.; MacNeille, Tress; Taylor, Russi; Winchell, April; Walt Disney Television Animation; Walt Disney Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2007)
Everyone's invited to Big Pete's Halloween party. But the gang needs to reach Trick-Or-Treat Tower before the moon is full or the gates will lock and the party will be over before it starts. Can they get through the foggy woods, past the Candy Corn Patch and over the drawbridge in time?
Mickey's treat -- Goofy the Great -- Doctor Daisy, M.D.
"Playhouse Disney"--Container.
Bonus features: Bonus episode, "A little Einsteins Halloween"; games and activities; DVD-ROM includes: Spooky Clubhouse cookbook; Creepy Clubhouse character stencils.
Voices: Wayne Allwine, Tony Anselmo, Dee Bradley Baker, Corey Burton, Jim Cummings, Bill Farmer, Tress MacNeille, Russi Taylor, April Winchell.
DVD, region 1, full screen (1.33:1) presentation; Dolby Digital surround, digitally mastered, dual-layer, NTSC.
DVD-ROM features: Computer capable of playing DVD movies, either running Microsoft Windows 95 or higher, or Macintosh system 8.6 or higher. Some features may require an Internet connection. This DVD will not work in a CD-ROM drive.
English, dubbed French and dubbed Spanish dialogue; English subtitles for the deaf and hard of hearing.
Keywords: Mickey Mouse (Fictitious character) -- Juvenile films; Halloween -- Juvenile films; Parties -- Juvenile films; Television programs; Children's television programs; Television series; Animated television programs; Action and adventure television programs; Video recordings for the hearing impaired; French language materials; Spanish language materials